Development of an Influenza/COVID-19 Combination mRNA Vaccine Containing a Novel Multivalent Antigen Design That Enhances Immunogenicity of Influenza Virus B Hemagglutinins - Elena Thornhill-Wadolowski; Dana L. Ruter; Feng Yan; Mayur Gajera; Evan Kurt; Labannya Samanta; Kimberlin Leigh; Jianbo Zhu; Zhijun Guo; Zihao Wang; Yuanqing Liu; Jaewoo Lee; et al. (Vaccines, 2025)
Background/Objectives: Developing next-generation mRNA-based seasonal influenza vaccines remains challenging, primarily because of the relatively low immunogenicity of influenza B hemagglutinin (HA) antigens. We describe a systematic vaccine development strategy that combined vector and antigen design optimization. Methods: Novel untranslated region (UTR) sequences and a hybrid poly(A) tail were used to increase plasmid stability and mRNA expression. Fusion proteins containing HA antigens linked by T4 foldon domains were engineered to enhance the immune responses against influenza B HA antigens and to permit the expression of multiple HA ectodomains from a single mRNA species. The vaccine performance was verified in a traditional encapsulated lipid nanoparticle (LNP) formulation that requires long-term storage at temperatures below −15 °C as well as in a proprietary thermo-stable LNP formulation developed for the long-term storage of the mRNA vaccine at 2–8 °C. Results: In preclinical studies, our next-generation seasonal influenza vaccine tested alone or as a combination influenza/COVID-19 mRNA vaccine elicited hemagglutination inhibition (HAI) titers significantly higher than Fluzone HD, a commercial inactivated influenza vaccine, across all 2024/2025 seasonal influenza strains, including the B/Victoria lineage strain. At the same time, the combination mRNA vaccine demonstrated superior neutralizing antibody titers to 2023/2024 Spikevax, a commercial COVID-19 comparator mRNA vaccine. Conclusions: Our data demonstrate that the multimerization of antigens expressed as complex fusion proteins is a powerful antigen design approach that may be broadly applied toward mRNA vaccine development.